Resource variation generates positive correlations between pre- and postcopulatory sexual traits. (21st December 2018) - Supriya, K; Price, Trevor D; Rowe, Melissah
Abstract: Male fertilization success depends on investment in both pre- and postcopulatory sexually selected traits, and considerable attention has recently been paid to quantifying the strength and direction of covariance between pre- and postcopulatory trait expression. Here, building upon previous sperm competition models, we theoretically investigate how variation in total investment into fertilization success, as well as differences in the form of precopulatory competition, influences the correlation between pre- and postcopulatory traits across species. We find that whenever species differ in the total investment into fertilization, optimal partitioning of investment typically generates positive correlations between sexual traits. This contrasts with the general expectation of a negative correlation based on the trade-off between investment in pre- and postcopulatory traits at the level of an individual. Nonetheless, negative correlations do arise under some conditions, notably when total investment into fertilization is similar across species and species vary in the form of precopulatory male–male competition along a continuum from dyadic contest to scramble competition. These results imply that the assessment of underlying trade-offs between pre- and postcopulatory trait investment requires an evaluation of how overall investment into total fertilization success varies across species. Abstract : To produce offspring, males must win a mate and successfully fertilize an egg, both of which require energy. This leads to the expectation that species whose males invest more into winning mates invest less into egg fertilization and vice versa. We show, however, that reproductive investment is often not an either-or proposition. Instead, an increase in the amount of energy invested into reproduction often results in additional investment into both winning mates and fertilizing eggs.